Mirror, mirror, am I the best player at all? Development of psychometric instruments assessing fantasy proneness and deflated reality in sport - Zhang, S.; Boardley, I. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Background: Competitive sport offers an excellent environment for an individual to fulfil the lionization of the self as one can have tremendous opportunities to beat opponents, dominate the competition, or at least fantasize about being an exceptional performer. Competitive sport is also a rocky way - one would not become a `talent` or an `elite` without thousands of hours of deliberate practice and training in a relatively tiring and tedious environment, whereas investing greater effort and working harder do not necessarily lead to more positive outcomes or a more promising career. In this research, we developed and validated two relevant psychometric instruments, namely the Sport Fantasy Proneness Scale (SFPS) and the Deflated Reality in Sport Scale (DRSS), to assess the important but overlooked context-specific constructs. Methods: We established a working definition for sport fantasy proneness and deflated reality in sport and generated an initial item pool of the SFPS and DRSS from well-established, relevant measures assessing the two constructs in general life domains, prior to a rigorous process of content validity assessment involving an expert panel. We then examined factorial, convergent, discriminant, and concurrent validity and measurement invariance, as well as internal consistency and test-retest reliability of the two new scales, through two cross-sectional samples (Study 1: Sample 1 N = 255, Sample 2 N = 260) and one longitudinal sample (Study 2: Sample 3 N = 118) of competitive athletes in the UK. Results: Aligning with the conceptualizations in general life domains, one`s disposition of engaging in sport fantasy and perception of deflated reality in sport both appear to be a unidimensional construct. Evidence supported the convergent, discriminant, and concurrent validity whilst demonstrating very good consistency, test-retest reliability, and measurement invariance of the two new scales. A weak, positive correlation exists for scores of the two new scales, and a mixed profile of sport fantasy proneness and sense of deflated reality in sport could exist (i.e., low-low, low-high, high-low, high-high). Thus, the two constructs may interactively influence training- and performance-related outcomes in sport. Conclusion: The SFPS and the DRSS demonstrated robust psychometric properties in assessing athletes` sport fantasy and perception of deflated reality. The new scales provide researchers and practitioners with new, reliable instruments to examine new research questions and tackle issues relevant to the two important but previously overlooked psychological constructs.